FORMATION AND DEVELOPMENT OF THE LEGAL INSTITUTION FOR STATE PROTECTION OF PARTICIPANTS IN CRIMINAL PROCEEDINGS - Stepanyan, Seda (State and Law, 2023)
The article is dedicated to the consideration of the issues of the formation and development of the institution of participant protection in criminal proceedings, ensuring the security of persons subject to state protection, both in European states and on the territory of the former USSR states. The article also discusses the development of the institution of protection of participants in criminal proceedings in Armenia and its role at the current state.
Keywords: criminal proceedings; safety; public/ state protection; special protection measures; crime victim; public interest; private interest